Optimized protocol for quantification of extracellular nicotinamide adenine dinucleotide: evaluating clinical parameters and pre-analytical factors for translational research - Saqr, Al-Hussein Ahmed; Kamali, Can; Brunnbauer, Philipp; Haep, Nils; Koch, Pia; Hillebrandt, Karl-Herbert; Keshi, Eriselda; Moosburner, Simon; Mohr, Raphael; Raschzok, Nathanael; Pratschke, Johann; Krenzien, Felix (Frontiers in Medicine, 2024)
Nicotinamide adenine dinucleotide(NAD+), a coenzyme for more than 500 enzymes, plays a central role in energy production, metabolism, cellular signaling, and DNA repair. Until recently, NAD+ was primarily considered to be an intracellular molecule(iNAD+), however, its extracellular species(eNAD+) has recently been discovered and has since been associated with a multitude of pathological conditions. Therefore, accurate quantification of eNAD+ in bodily fluids such as plasma is paramount to answer important research questions. In order to create a clinically meaningful and reliable quantitation method, we analyzed the relationship of cell lysis, routine clinical laboratory parameters, blood collection techniques, and pre-analytical processing steps with measured plasma eNAD+ concentrations. Initially, NAD+ levels were assessed both intracellularly and extracellularly. Intriguingly, the concentration of eNAD+ in plasma was found to be approximately 500 times lower than iNAD+ in peripheral blood mononuclear cells(0.253±0.02 µM vs 131.8±27.4 µM; p=0.007, respectively). This stark contrast suggests that cellular damage or cell lysis could potentially affect the levels of eNAD + in plasma. However, systemic lactate dehydrogenase in patient plasma, a marker of cell damage, did not significantly correlate with eNAD+(n=33; r=-0.397; p=0.102). Furthermore, eNAD+ was negatively correlated with increasing c-reactive protein(CRP, n=33; r=-0.451; p=0.020), while eNAD+ was positively correlated with increasing hemoglobin(n=33; r=0.482; p=0.005). Next, variations in blood drawing, sample handling and pre-analytical processes were examined. Sample storage durations at 4°C(0-120 min), temperature(0°to 25°C), cannula sizes for blood collection and tourniquet times (0-120s) had no statistically significant effect on eNAD+(p>0.05). On the other hand, prolonged centrifugation(>5 min) and a faster braking mode of the centrifuge rotor(<4 min) resulted in a significant decrease in eNAD+ levels(p<0.05). Taken together, CRP and hemoglobin appeared to be mildly correlated with eNAD + levels whereas cell damage was not correlated significantly to eNAD+ levels. The blood drawing trial did not show any influence on eNAD+ , in contrast, the preanalytical steps need to be standardized for accurate eNAD+ measurement. This work paves the way towards robust eNAD+ measurements, for use in future clinical and translational research, and provides an optimized hands-on protocol for reliable eNAD+ quantification in plasma.